Changing milk production trends in Peru - Bernet, T.; Staal, Steven J.; Walker, T. (International Mountain Society (IMS) and United Nations University, 2001)
In Peru, strong growth in urban demand for industrially processed dairy products has induced a rapid increase in milk production along the coast but not so much in the Andean highlands, where an increase in milk production would create the greatest benefits. A farm–household optimisation model was used to assess the current and changing competitiveness of milk production on the coast (Arequipa and Lima) and in the highlands (Cajamarca). Results show that large farms on the coast, particularly near Lima, are currently the most profitable. However, the high milk prices in Lima are likely to fall because of local market saturation and reduced competition among regional milk buyers. In contrast, milk prices in Arequipa and Cajamarca are expected to rise as a result of increased milk collection by milk processors since milk production costs in these regions are lower and there is a strong incentive to increasingly substitute expensive imported milk powder with locally produced evaporated milk. Improvements in the rural road system and the promotion of agricultural export crops along the coast, particularly in Arequipa, would accelerate the expansion of milk production in the highlands. To improve highland farmers' access to the market, policy makers and development agencies should target their interventions in close collaboration with milk processors. Because they have a strong interest in increasing milk production in their own region, milk processors are also important partners when designing measures to improve farmers' fodder and herd management practices in order to further increase the competitiveness of milk production in the highlands relative to the coast.